2000
DOI: 10.1103/physrevlett.85.186
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetism below the Stoner limit in La-DopedSrB6

Abstract: Spin-polarized band calculations for LaSr 7 B 48 show a weak ferro-magnetic state. This is despite a low density-of-states (DOS) and a low Stoner factor. The reason for the magnetic state is found to be associated with a gain in potential energy in addition to the exchange energy, as a spin-splitting is imposed. An impurity like La DOS is essential for this effect. It makes a correction to the Stoner factor, and provides an explanation of the recently observed weak ferro-magnetism in doped hexaborides.Recent e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 16 publications
1
24
1
1
Order By: Relevance
“…This explanation requires that the exciton binding energy should be comparable in size to the single-particle band gap. Jarlborg suggested [6] that the magnetism may be conventional itinerant magnetism. Although magnetism in materials which do not have partly filled 3d, 4f, or 5f shells is rare, it is not unprecedented.…”
mentioning
confidence: 99%
“…This explanation requires that the exciton binding energy should be comparable in size to the single-particle band gap. Jarlborg suggested [6] that the magnetism may be conventional itinerant magnetism. Although magnetism in materials which do not have partly filled 3d, 4f, or 5f shells is rare, it is not unprecedented.…”
mentioning
confidence: 99%
“…The 80-site cell calculation of LaSr 7 B 48 using 20 kpoints and the large basis, finds a small moment of 0.10 µ B /cell, which is about 10 mRy/supercell lower in total energy than the paramagnetic solution 10 . If fewer kpoints are used, one finds that the (paramagnetic) DOS and its energy derivative near E F are larger, cf Table 1.…”
Section: B Magnetismmentioning
confidence: 94%
“…The effects can be larger in a compound as long as the different sub-bands and the ionicity of the system show favorable conditions. In a recent work we showed that LaSr 7 B 48 is likely to be such a system 10 . Here we extend these calculations to larger unit cells, to different types of dopants, and give a more complete discussion of the results.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations